Risk Disclosure Practices among Malaysian Listed Firms - Zadeh, Farahnaz Orojali; Abdul Rasid, Siti Zaleha; Basiruddin, Rohaida; Zamil, Nor Aiza Mohammmed; Vakilbashi, Amin (International Journal of Economics and Financial Issues, 2016)
This study discusses the development of risk disclosure policy in Malaysia after the 1997 financial crisis and provides evidence on the importance of risk disclosure over the recent years. Analysis on the trend of risk disclosure based on the new development was carried out through content analysis. The findings show positive trend of development in risk disclosure practices in Malaysia over the period of 2001-2011. In addition, risk disclosure sentences were found to be insufficient and should be rectified. There is a need to revisit the current regulations and standards to improve the risk disclosure practices and to follow internationally-based accounting policy. Keywords: Risk Disclosure, Regulatory, Malaysia JEL Classification: M40